Aerobiology Over Antarctica – A New Initiative for Atmospheric Ecology - Pearce, David A.; Alekhina, Irina A.; Terauds, Aleks; Wilmotte, Annick; Quesada, Antonio; Edwards, Arwyn; Dommergue, Aurelien; Sattler, Birgit; Adams, Byron J.; Magalhães, Catarina; Chu, Wan-Loy; Lau, Maggie C. Y.; et al. (Frontiers in Microbiology, 2016)
The role of aerial dispersal in shaping patterns of biodiversity remains poorly understood, mainly due to a lack of coordinated efforts in gathering data at appropriate temporal and spatial scales. It has been long known that the rate of dispersal to an ecosystem can significantly influence ecosystem dynamics, and that aerial transport has been identified as an important source of biological input to remote locations. With the considerable effort devoted in recent decades to understanding atmospheric circulation in the south polar region, a unique opportunity has emerged to investigate the atmospheric ecology of Antarctica, from local to continental scales. This concept note identifies key questions in Antarctic microbial biogeography and the need for standardized sampling and analysis protocols to address such questions. A consortium of polar aerobiologists is established to bring together researchers with a common interest in the airborne dispersion of microbes and other propagules in the Antarctic, with opportunities for comparative studies in the Arctic.